Development of mental health and psychosocial support (MHPSS) guidelines for deaf and hard of hearing children in the Gaza Strip. - Nathaniel Scherer; Ramadan Hussein; Julian Eaton; Naim Kabaja; Ritsuko Kakuma; Tracey Smythe; Sarah Polack (Public Library of Science (PLoS), 2023)
Deaf and hard of hearing children in the Gaza Strip may be at risk of mental health conditions and psychological distress, as a result of social exclusion and limited accessible communication. This article presents the process and research methods used to develop guidelines for schools in the Gaza Strip on mental health and psychosocial support for deaf and hard of hearing children. The process was guided by the GIN-McMaster guideline development checklist across four steps: (1) priority settings; (2) searching for evidence; (3) developing recommendations; (4) evaluation. Priority setting was spearheaded by local and international researchers, and a local steering committee comprised of deaf and hard of hearing representatives, school administration and staff, mental health specialists, family members and government officials. In searching for evidence, and in order to generate evidence-based recommendations for the guidelines, we utilised a scoping review of global mental health support for deaf and hard of hearing children and qualitative research with deaf and hard of hearing children and adults, families and teachers. Two pilot studies were conducted in mainstream and specialist educational settings as way of evaluation. The scoping review and qualitative research identified various content for the guidelines, including the importance of information on disability and deafness, promoting social inclusion and self-esteem, and accessible learning environments. The pilot studies demonstrated feasibility and acceptability among teachers and deaf and hard of hearing children, although teachers need sufficient support and resources to implement. Now finalised, the guidelines are being distributed to schools in the Gaza Strip to support the mental health and wellbeing of deaf and hard of hearing children.